1994
DOI: 10.1161/01.cir.89.6.2667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiofrequency catheter ablation on regional myocardial blood flow. Possible mechanism for late electrophysiological outcome.

Abstract: RF catheter ablation not only results in a marked reduction in blood flow within the acute pathological lesion but also causes reduced flow beyond the borders of the acute lesion because of microvascular endothelial cell injury. The progression or resolution of tissue injury within the region beyond the border of the pathological lesion may explain the late electrophysiological effects of RF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
2
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 18 publications
2
44
2
4
Order By: Relevance
“…The possibility that intramyocardial vasculature can alter RF lesion morphology through convective heat loss has not been explored previously. This concept differs from the work of Nath et al, 14 who demonstrated impaired circulation at the microscopic level immediately around RF lesions.…”
Section: Discussioncontrasting
confidence: 75%
“…The possibility that intramyocardial vasculature can alter RF lesion morphology through convective heat loss has not been explored previously. This concept differs from the work of Nath et al, 14 who demonstrated impaired circulation at the microscopic level immediately around RF lesions.…”
Section: Discussioncontrasting
confidence: 75%
“…As previously reported and demonstrated in this study, although tip temperatures dropped instantaneously with termination of RF energy, tissue temperatures may continue to be elevated. 15,[23][24][25] Mechanistically, this is thought to result from 2 different heating processes. First, there is rapid resistive heating of a thin layer of tissue around the catheter tip during ablation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Nath et al demonstrated that tissues next to the site of RF ablation show thermal injury, which might progress to have late effects on AV conduction. 15 Another possible mechanism of AV block in the present case might be the result of the propafenon therapy; however, the patient took 150 mg of propafenone only once and her AV block persisted for 1 week. Considered together, we speculate that all these factors (pre-existing first-degree AV block, modulation of AV node by the ablation, and propafenone) may have contributed to the occurrence of a complete AV block.…”
Section: Discussionmentioning
confidence: 67%